2022
DOI: 10.3389/fgene.2022.849206
|View full text |Cite
|
Sign up to set email alerts
|

Causal Effects of Genetically Predicted Cystatin C on Osteoporosis: A Two-Sample Mendelian Randomization Study

Abstract: Objectives: Although it has long been reported that high levels of cystatin C could contribute to the development of osteoporosis in some studies, no evidence has established a causal association between them thus far.Methods: A Mendelian randomization (MR) study was conducted to determine the causal effect of cystatin C on osteoporosis based on public databases obtained from separately published genome-wide association studies (GWASs). The single-nucleotide polymorphisms (SNPs) for cystatin C were extracted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…29,30 A Mendelian randomization study of MR-Base and UK Biobank data showed significant correlations between serum cystatin C levels and osteoporosis. 5 According to a cross-sectional Korean study, serum cystatin C concentrations were inversely correlated with BMD among women, but not men. Women with a higher cystatin C level were more likely to have osteoporosis, whereas men did not show such a correlation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29,30 A Mendelian randomization study of MR-Base and UK Biobank data showed significant correlations between serum cystatin C levels and osteoporosis. 5 According to a cross-sectional Korean study, serum cystatin C concentrations were inversely correlated with BMD among women, but not men. Women with a higher cystatin C level were more likely to have osteoporosis, whereas men did not show such a correlation.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 As the population ages, osteoporosis is becoming more prevalent, 3,4 affecting approximately 200 million people worldwide. 5 Currently, osteoporosis is clinically indicated by measuring bone mineral density (BMD) through dual-energy X-ray absorptiometry (DXA). 6,7 However, further exploration of biomarkers related to bone health and density might aid in the early diagnosis, prevention, and treatment of osteoporosis.…”
Section: Introductionmentioning
confidence: 99%
“…Using the package twosampleMR (Yuan et al, 2022) in R software, all analyses were conducted. According to the P-value of 5 × 10 −8 , the SNPs (IVs) in the GWAS were identified.…”
Section: Statistical Analysismentioning
confidence: 99%